Effect of Information and Communication Technology on the Interest and Achievement of Secondary School Students in Chemistry in Aguata Education Zone - Ezeiheukwu, Chika Mary; Okongwu, Dozie John Okongwu; Ibe, Franklin Nnanna (Strata International Journal of Social Issues, 2024)
This research work investigates the impact of Information and Communications Technology instructional methods on the interest and performance in Chemistry by Senior Secondary School Students within Aguata Education Zone of Anambra State. The research design that was used in the study is a quasi-experimental pre-test, post-test and control group design from an intact class. Four research questions were raised and three hypotheses were tested at 0. 05 level of significance. The population of the study therefore included 2,644 Senior Secondary School Students Class Two from nine out of the 52 public schools in Aguata Education Zone. Chemistry Interest Inventory (CII) was the instrument used for data collection while Chemistry Achievement Test (CAT) was also used and these two were analyzed using Cronbach Alpha and Kuder- Richardson (K-20) respectively revealed a reliability coefficient of CII is 0.64) and the reliability coefficient of CAT is 0.73. For the research questions, mean and standard deviation were used to analyze the collected data. The hypotheses were tested at 0. 05 level of significance using analysis of covariance. The findings revealed that there was a significant improvement in students’ cognitive achievement and interest in chemistry due to ICT instructional packages. And, that gender does not affect the performance of students that were taught Chemistry with ICT instructional package. In light of this, it was recommended that Chemistry teachers should adopt ICT constructional methods in the teaching of Chemistry in Senior Secondary Schools.